PEMAHAMAN KONSEP AGRESI INTERNASIONAL: ANALISIS TERHADAP KERANGKA HUKUM INTERNASIONAL - Khasanah, Isvania; Rahayu, Dita; Hendrawati, Sulkiah (LPPM Universitas Bina Bangsa, 2024)
This research aims to delve into and analyze the concept of international aggression within the framework of international law. International aggression poses a serious issue that can trigger conflicts between nations and jeopardize global peace. Through the lens of international legal analysis, this study explores key aspects related to the definition, characteristics, and consequences of international aggression. The research employs a method of analyzing international legal documents, including the UN Charter and relevant treaties, to identify the concept of international aggression and the legal framework regulating it. In-depth analysis of the development of these legal norms helps in understanding how the international community strives to prevent and address acts of aggression. The findings of the study highlight challenges in the interpretation and application of legal norms related to international aggression. Furthermore, the research discusses the role of international institutions, particularly the UN, in handling aggression cases and maintaining world peace. The legal implications of aggressive actions and efforts to enforce international law are reexamined within the context of real-world cases to provide deeper insights. By presenting a comprehensive analysis of the concept of international aggression, this research is expected to contribute to a better understanding of the complexity of this issue. Its implications are anticipated to assist policymakers, researchers, and legal practitioners in enhancing the effectiveness of international law in addressing the challenges of international aggression, ultimately contributing to global peace and justice